Udûl kavramına üslûbu'l-Kur'ân çerçevesinde yaklaşım : Temmâm Hassân El-Beyân Fî Revâi'i'l-Kur'ân örneği - Atay, Munise Betül (My University, 2023)
Udûl, bir asıldan çıkmak veya kurala muhalefet etmek olarak tanımlanabilir. Çalışmamızda dilbilim ve edebiyat araştırmalarında konu edinilen udûl kavramını Kur’ân ilimlerinden olan üslûbu’l-Kur’ân ilmi açısından ele aldık. Temmâm Hassân, el-Beyân fî revâi’i’l-Kur’ân adlı eserinde ‘el-uslûbu’l-udûlî’ başlığı altında udûl kavramına yer vermiş ve bu kavrama özgün yaklaşımlarda bulunmuştur. Çalışmamız hem udûl kavramının Kur’ân dil ve üslûp özellikleri bakımından önemini hem de Temmâm Hassân’ın bu kavramla ilgili özgün yaklaşımlarını ortaya koyması bakımından alana katkı sağlamayı amaçlamaktadır. Çalışmamız üç bölümden oluşmaktadır. Birinci bölümde Temmâm Hassân ve el-Beyân fî revâi’i’l-Kur’ân adlı eseri tanıtılmıştır. İkinci bölümde çalışmamızın temel kavramlarından olan üslûp, üslûpbilim, üslûbu’l-Kur’ân ve udûl kavramları ele alınmıştır. Üçüncü bölümde ise Temmâm Hassân’ın udûl kavramına yaklaşımı ortaya konulup karineler üzerinden ele aldığı örnekler incelenmiştir. Bu ayet örneklerinin üslûp-udûl açısından analizi yapılmıştır. Tezimizde gerçekleştirdiğimiz incelemeler sonucunda udûl, kavramının genelde üslûp incelemeleri özelde Kur’ân üslûbunda önemli bir yere sahip olduğu tespit edilmiştir.

Odool can be defined as going out of an original or breaking a rule. In our study, we discussed the concept of odool, which is the subject of linguistics and literature studies, in terms of the science of style, which is one of the Qur'anic sciences. Tammâm Hassân, in his work al-Beyân fî rawâi'i'l-Kur'an, included the concept of odool under the title of 'el-uslûbu'l-udûlî' and found original approaches to this concept. Our study aims to contribute to the field in terms of both the importance of the concept of odool in terms of the language and style features of the Qur'an and the original approaches of Tammâm Hassân about this concept. Our work consists of three parts. In the first part, the work of Tammâm Hassân and al-Beyân fî rawâi'i'l-Kur'an has been introduced. In the second part, the concepts of style, stylistics, style of the Qur'an and odool, which are the basic concepts of our study, are discussed. In the third chapter, Tammâm Hassân's approach to the concept of odool is revealed and the examples he deals with on presumptions are examined. These verse examples were analyzed in terms of style and odool. As a result of the examinations we have carried out in our thesis, it has been determined that the concept of odool has an important place in stylistic studies in general and in the style of the Qur'an in particular.
Approach to the concept of odool in the frame of the style of the Qur’an : the example of Tammâm Hassân Al-Beyân Fî Rawâ’i’l Qur’ân
Keywords: al-Beyân fî rawâi'i'l-Kur'an; Anlama çalışmaları; Comprehension studies; Criticism, interpretation, etc; Deviation from the Norm; Dil, Üslup; el-Beyân fî revâi’i’l-Kur’ân. The Qur'an; Eleştiri, yorum, vb; Hermeneutics; Koran; Kur’ân; Kur’ân Üslûbu; Kur'an-ı Kerim; Language, style; Normdan Sapma; Odool; Qur'an; Qurʼan; Stylistics; Tafsir; Tammâm Hassân; Tefsir; Tefsirler; Temmâm Hassân; The Style of Qur'an; Udûl; Üslûpbilim